Story Telling to Character Building through “Literasi IRAMA” in TK Anak Cerdas - Dwi Susanti; Sofia Mariana; Elis Dwi Yani (Pancaran Pendidikan, 2021)
Reading is an important activity in Literacy program for Early Childhood Education. This activity is connected with reading and book where they really don’t understand how to use it at the first time. It is started when a child has a new story book in his hands or when his parents read a book for him. The interaction between children and parents is such a wonderful time for both of them. It also has an important component in building positive character with playfulness activity where language is used for having fun. Literasi Irama is one of Literacy Program of TK Anak Cerdas Ungaran where it is a school – parents Co Parenting Program to build positive character for children. The parents may read the story book and retell to their children the moral character value from the story and the character within it.